2020
DOI: 10.12659/msm.925844
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Prediction Model for Postoperative Ovarian Sex Cord-Stromal Tumor Patients

Abstract: Background We developed a nomogram for prognostic prediction of overall survival (OS) in postoperative ovarian sex cord-stromal tumor (SCST) patients and discuss the effect of chemotherapy at various FIGO stages. Material/Methods SCST patients after surgery from 2004 to 2015 were enrolled from the Surveillance, Epidemiology and End-Results (SEER) database, matched into pairs by propensity score matching (PSM), and divided into a training set and a validation set. Univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The internal validation confirmed that the nomogram was highly accurate in predicting premature death and helpful in screening patients with high clinical risk with high practicality [18]. You et al [19] included 506 eligible patients with postoperative ovarian sex cord-stromal tumor (SCST) from the SEER database. They constructed and validated the OS nomogram, which showed that it was more practical than FIGO staging [19].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The internal validation confirmed that the nomogram was highly accurate in predicting premature death and helpful in screening patients with high clinical risk with high practicality [18]. You et al [19] included 506 eligible patients with postoperative ovarian sex cord-stromal tumor (SCST) from the SEER database. They constructed and validated the OS nomogram, which showed that it was more practical than FIGO staging [19].…”
Section: Discussionmentioning
confidence: 91%
“…You et al [19] included 506 eligible patients with postoperative ovarian sex cord-stromal tumor (SCST) from the SEER database. They constructed and validated the OS nomogram, which showed that it was more practical than FIGO staging [19].…”
Section: Discussionmentioning
confidence: 99%
“…Marital status was found to be an independent prognostic factor in patients with ovarian sex cordstromal cancer [18] and gastric adenocarcinoma [19]. Assessment of the relationship between marital status and OS in patients with mGC who underwent surgery found, however, that marital status was not associated with OS.…”
Section: Discussionmentioning
confidence: 94%
“…Analysis stratified by stage found that stages IA and IB patients who received chemotherapy had poor OS, while OS showed no significant difference in patients with other stages. 72 This deleterious effect of chemotherapy may be due to ineffective chemotherapeutic regimens, side effects, and individual differences in patients’ tolerance to chemotherapy. The unfavorable results of chemotherapy indicate the need for further exploration.…”
Section: Chemotherapymentioning
confidence: 99%